The Influence of Job Promotion and Work Environment on The Work Performance of Employees of The Cooperative and SME Department of Palembang City - Husnul Hotimah; Fauziah Afriyani; Emilda Emilda (ProBisnis : Jurnal Manajemen, 2023)
This study aims to determine whether there is an effect of position promotion and work environment on the work performance of employees of the Palembang City Cooperative and SME Office. This research is quantitative descriptive research. The population and sample in this study were 40 people from the employees of the Palembang City Cooperative and SME Office. The sampling technique in this study used saturated sampling technique. Data were collected by distributing questionnaires and then analysed using SPSS version 24. The results of this study indicate that there is an effect of position promotion and work environment on the work performance of employees of the Palembang City Cooperative and SME Office. Position Promotion and Work Environment together affect the work performance of employees of the Palembang City Cooperative and SME Office.